Comparison of Salbutamol Delivery Efficiency for Jet versus Mesh Nebulizer Using Mice - Kyung Hwa Chang; Sang-Hyub Moon; Jin Young Oh; Young-Soon Yoon; Namyi Gu; Chi-Yeon Lim; Bong Joo Park; Ki Chang Nam (MDPI AG, 2019)
Recent reports using a breathing simulator system have suggested that mesh nebulizers provide more effective medication delivery than jet nebulizers. In this study, the performances of jet and mesh nebulizers were evaluated by comparing their aerosol drug delivery efficiencies in mice. We compared four home nebulizers: two jet nebulizers (PARI BOY SX with red and blue nozzles), a static mesh nebulizer (NE-U22), and a vibrating mesh nebulizer (NE-SM1). After mice were exposed to salbutamol aerosol, the levels of salbutamol in serum and lung were estimated by enzyme linked immunoassay (ELISA). The residual volume of salbutamol was the largest at 34.6% in PARI BOY SX, while the values for NE-U22 and NE-SM1 mesh nebulizers were each less than 1%. The salbutamol delivery efficiencies of NE-U22 and NE-SM1 were higher than that of PARI BOY SX, as the total delivered amounts of lung and serum were 39.9% and 141.7% as compared to PARI BOY SX, respectively. The delivery efficiency of the mesh nebulizer was better than that of the jet nebulizer. Although the jet nebulizer can generate smaller aerosol particles than the mesh nebulizer used in this study, the output rate of the jet nebulizer is low, resulting in lower salbutamol delivery efficiency. Therefore, clinical validation of the drug delivery efficiency according to nebulizer type is necessary to avoid overdose and reduced drug wastage.